RETHINGKING GAGASAN DAN PEMBAHARUAN MUHAMMAD ABDUH DI MESIR RELEVENSINYA DENGAN MASADEPAN PENDIDIKAN ISLAM - *, Manijo (Pascasarjana IAIN Kudus, 2013)
Muhammad Abduh was an Egyptian reformer who emphasized renewal thought or effort to respond to the challenges that comefrom the West and the modern world, chosen identifikatif approachis evidence for a creative and proactive stance in solving variousproblems of Muslims. With indentifikatif approach it uses,Muhammad Abduh be seen as a reformer who thought renewalcharacterized by or having typology of modernist-reformist. Agendalaunched by Muhammad Abduh in order to carry out its renewal is;purification, reform, reformulation and defense of Islam. MohammadAbduh spirit of renewal at this time , may need to be rethought asembryonic restoration of Egypt in general and Islamic education(al-Azhar) in particular, so that the later ending especially Islamiceducation in Indonesia as a base capable successor even struggle reform ideals of Muhammad Abduh. Who knows Qibla Thought advancement and progress of Islamic education can be switchedand started from Indonesia.